That is how Allah wants us to care - Seise, Claudia (Azizah) (AboutIslam, 2019)
A few days ago, I attended my first funeral prayer in a mosque. It was conducted right after the mid-day prayer. The dead person was brought into the mosque in a coffin and placed in front of the imam.